PERAN STRATEGIC PLANNER DAN DATA EXECUTIVE DALAM KAMPANYE “TERBUKA UNTUK SEMUA, BERGERAK BERSAMA WARGA #KULIKDIPORTALSAMAWA” SEBAGAI UPAYA BRAND COMMUNICATION UNTUK MENINGKATKAN BRAND AWARENESS DAN USER PORTAL SEMARANG SATU DATA DAN SAMAWA (SEMUA DATA UNTUK WARGA) - Aiko Hanantyo Putri; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2026)
Portal Semarang Satu Data and SAMAWA (Semua Data Untuk Warga), as public data services managed by the Statistics Division of the Semarang City Communication and Informatics Office (Diskominfo), faced the issue of low public awareness, which consequently affected the limited utilization of the services. This project aimed to address the issue through a campaign entitled “Terbuka Untuk Semua, Bergerak Bersama Warga #KulikdiPortalSAMAWA,” with the objective of increasing brand awareness and the number of users of both services. The campaign was designed using an Integrated Marketing Communication (IMC) approach by integrating media channel optimization, event marketing, direct marketing, and digital publication through Instagram @samawa.smg. The implementation involved the roles of Strategic Planner and Data Executive, responsible for formulating the big idea, designing the event-based program concept and technical scheme, and analyzing campaign survey data. The evaluation results indicate a 30,8% increase in awareness of Portal Semarang Satu Data, accompanied by and additional 127.242 website visitors, as well as a 62,7% increase in awareness of SAMAWA and 19 data requests submitted through the service.